Power Game Experienced by Christine Collins In Changeling Film - Kurniawan Henky; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2014)
In Changeling film, Collins as the female character experiences injustice. In this study, I want to reveal how the authorities abuse their power to Collins and the strategies that used by Collins to defeat the authorities’ power. I will use the concept of abuse by the powerful to the powerless by Adam M. Tomison and Joe Tucci and power relations by Michel Foucault. I find out that power is easily abused and not stable because one time, it is the authorities that have the power, but at the other time, it is individual who has more power. The police and the doctors abuse their power to Collins. I find out that Collins uses some strategy to defeat the authorities’ power. She is complying, gathering evidence, and getting allies. At first, she is powerless, but in the end, Collins can defeat the authorities’ power and become powerful.